Penerapan Pendidikan Jarak Jauh (PJJ) Dimasa Pandemi Covid-19 pada SIDH Belanda dan SIKL Malaysia - Husni Mubarok; Yasinta Indra Swastika; Ayu Ainun; Siti Umi Hamdanah; Putri Diana Lestari; Muhammad Alif Saifuddin (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
The covid-19 pandemic caused the elimination of all activities that are usually carried out by almost everyone in the world, especially learning activities at various levels. Based on the Higher Education Law number 12 of 2012, article 31 concerning Distance Education (PJJ) is a learning process that is carried out remotely through the use of various communication and information media. Therefore, since the covid outbreak, distance education is now widely applied in the learning process almost all over the world. This study aims to determine the application of distance education in SIDH Netherlands and SIKL Malaysia during the pandemic, and to find out the obstacles in the application of distance education in SIDH Netherlands and SIKL Malaysia during the pandemic. The method used in this research is descriptive qualitative method. Data collection techniques in this study using interview techniques. The results of the study state that SIDH in the Netherlands and SIKL Malaysia have implemented the PJJ (Distance Education) system since 2008, with Distance Learning being used to do this, automatically during this pandemic, students are not surprised by the online learning provided. teachers (educators), but there are also some obstacles faced during the teaching and learning process during the pandemic. Whereas in SIKL Malaysia, distance education was implemented when there was covid-19, so all students study at their respective homes. In its application, there are several obstacles in the learning process, one of which is signal constraints. The teachers from the two scools have coshen the best method for their students so that learning can be carried out optimally. And it is hoped that in learning to apply health protocols so that students and teacherscan carry out learning activities comfortably.